(untitled) (La U Investiga, 2022)
The evaluation of nutritional status in children under 6 months of age depends mainly on the type of breastfeeding used. Objective: To relate nutritional status and the type of breastfeeding used in children from 0 to 6 months of age. Methodology: Cross-sectional correlational study in the Health Center No. 1-Ibarra during the month of March 2022, 157 infants between 0 to 6 months were selected under specific criteria. Data corresponding to the mother and child were collected by means of a directed survey, the nutritional status was evaluated by means of growth curves and weight and length measurements. The data were collected in SPSS version 26 and the relationship between the variables was established through Fisher’s exact test. Results: the use of exclusive breastfeeding was related to normality (85%) and obesity (0.9%). Mixed breastfeeding was related to obesity (9.5%), risk of overweight (19%) and normality (57.1%). Contrasting, artificial breastfeeding presented relationship with chronic malnutrition (50%). Conclusions: There is a relationship between the nutritional assessment of normality and exclusive breastfeeding, followed by the risk of overweight and obesity attributed to the use of mixed breastfeeding, ending with chronic malnutrition and artificial breastfeeding. Exclusive breastfeeding is the most commonly used. The beginning of work or student activities and breast pathologies are the main reasons that prevent the use of exclusive breastfeeding. Key words: nutritional status, chronic malnutrition, obesity, exclusive breastfeeding, types of breastfeeding.